Fibroblastos periodontais humanos em meio de cultura suplementado com IL-1ß no modelo de força compressiva estática continua - Miguel, Delaini Pires Roman [UNIFESP] (2016)
Introduction: The mechanotransduction may be a cellular differentiation mechanism for fibroblasts that are derived from the periodontal ligament as well as local inflammation may also play an important role in the molecular response of these cells. Objective: Evaluate the viability, apoptosis, necrosis and gene expression of proinflammatory markers in a continuous static compression model using a proinflammatory cell culture. Methods: We selected 10 patients that were submitted to third molars extractions to obtain 4 mm2 of periodontal tissue of the middle third of their roots. Fibroblasts were isolated and expanded until the 6th passage and cultured in proinflammatory culture (IL- 1beta 5 ng / mL ) and after this three groups were formed according to the applied load: Control Group (CG), no charge; Experimental Group 1 (SG1), continuous static compression of 3g/6h and Experimental Group 2 (SG2) continuous static compression 4g/6h. Results: The cell viability control group had higher results both experimental groups, and was not observed differences between experimental groups. The cell apoptosis was higher in the experimental group 2 compared to the control and experimental groups 1, with no differences between them. No differences were observed between the groups in relation to cell necrosis. In gene expression not detected in the TNF-alpha expression, but IL-6 expression, this expression equal among all groups. Conclusion: Human periodontal fibroblasts in culture medium supplemented with IL-1 beta in continuous static compressive force model showed decreased cell viability, increased apoptosis and necrosis showed no changes and gene expression of IL-6 and TNF-alpha.